Efficient phosphate removal from water using ductile cast iron waste: a response surface methodology approach - Roushdy, Mai Hassan; Elkhashab, Nada Amr; Osman, Ahmed Ibrahim; Ali, Dalia Amer (Frontiers in Chemistry, 2024)
Water scarcity is a critical issue worldwide. This study explores a novel method for addressing this issue by using ductile cast iron (DCI) solid waste as an adsorbent for phosphate ions, supporting the circular economy in water remediation. The solid waste was characterized using XRD, XRF, FTIR, and particle size distribution. Wastewater samples of different phosphate ion concentrations are prepared, and the solid waste is used as an adsorbent to adsorb phosphate ions using different adsorbent doses and process time. The removal percentage is attained through spectrophotometer analysis and experimental results are optimized to get the optimum conditions using Design Expert V13. The pseudo-second order (PSO) kinetics model and Langmuir isotherm were fitted with the experimental results with maximum adsorption capacity (qmax = 0.28 mg/g). The thermodynamic analysis indicated that this adsorption process was spontaneous based on the negative value of Gibbs free energy (∆G). Additionally, the positive values of enthalpy (∆H) indicated the endothermic nature of this adsorption system. It was able to reach the highest adsorption percentage of 98.9 (%) for phosphate ions from aqueous solutions using response surface methodology (RSM) with optimum conditions of 10 mg/L phosphate ion concentration, pH = 8, normal room temperature, 9 min adsorption, and 0.5 g/L adsorbent dosage.